Pharyngeal Colonization by Streptococcus pneumoniae in Older Children and Adolescents in a Geographical Area Characterized by Relatively Limited Pneumococcal Vaccination Coverage. Issue 4 (April 2015) - Principi, Nicola; Terranova, Leonardo; Zampiero, Alberto; Montinaro, Valentina; Ierardi, Valentina; Peves Rios, Walter; Pelucchi, Claudio; Esposito, Susanna
Abstract : Background: The aim of this study was to evaluate the relation between colonization and vaccination status with pneumococcal conjugate vaccine (PCV) in older children and adolescents living in an area characterized by relatively limited vaccination coverage. Methods: Oropharyngeal swabs were obtained from 2076 randomly selected healthy school-age children and adolescents, and the extracted genomic DNA was tested for Streptococcus pneumoniae by means of real-time polymerase chain reaction. All of the positive cases were subsequently serotyped, and the association between vaccination status with the heptavalent PCV (PCV7) and pneumococcal colonization was determined. Results: S. pneumoniae was identified in the oropharyngeal swabs of 1201 subjects (57.9%), and its prevalence declined with age (74.9% in subjects aged <10 years, 51.8% in those aged 10–14 years and 32.7% in those aged ≥15 years; P < 0.001). There were more carriers of any pneumococcal serotype, any of the serotypes in PCV7, or any of the 6 additional serotypes in 13-valent PCV (PCV13) among the vaccinated than the unvaccinated subjects, but no association emerged after adjustment for age and other selected covariates. Sub-analyses by serotype and age groups revealed significant differences in the case of serotypes 3 and 19A among children aged <10 years (odds ratios of 2.03 and 2.18, respectively). Conclusions: These results show the absence of any long-term effect of PCV7 on colonization, and raise doubts concerning the recent suggestion to use carriage to evaluate the efficacy of PCVs. The high prevalence of carriers in all of the age groups independent of previous pneumococcal vaccination indicates that further studies are needed to evaluate whether the extensive use of PCVs in healthy older children and adolescents might reduce pharyngeal colonization of these subjects thereby increasing herd immunity.